Early Pseudomonas aeruginosa colonization in cystic fibrosis patients - Ocak, E.; Tugcu, G. D.; Polat, S. Eryilmaz; Cinel, G.; Emiralioglu, N.; Yalcin, E.; Ersoz, D. Dogru (European Respiratory Soc Journals Ltd, 2022)
[Abstract Not Available]
International Congress of the European-Respiratory-Society (ERS) -- SEP 04-06, 2022 -- Barcelona, SPAIN
Keywords: Bacteria; Children